The Silent Mill - Sudermann, Hermann, 1857-1928 (Salt Lake City, UT : Project Gutenberg, 2010)
"The Silent Mill" by Hermann Sudermann is a novel written in the early 20th century. The story revolves around the Rockhammer family, particularly the two brothers, Martin and Johannes, as they navigate the complexities of life, love, and tragedy in a small rural setting. It delves into themes of familial bonds, emotional struggles, and the impacts of past events on the present. At the start of the narrative, readers are introduced to the dilapidated old mill owned by the Rockhammer family, a symbol of both their heritage and misfortune. The story flashes back to describe the family's history, including the violent temper of the patriarch, Rockhammer, the tragic fate of one of Martin's brothers, and the subsequent innocence lost by him after the incident that rendered his brother unable to speak. As Martin matures alongside Johannes, they develop a close relationship, though tensions arise with Martin's new marriage to Trude and Johannes feelings towards her. The opening captures the quiet yet poignant moments of their lives, setting the stage for deeper emotional conflicts that unfold as relationships become increasingly complicated. (This is an automatically generated summary.)
Release date is 2010-11-22
Produced by Charles Bowen, from page scans provided by the Web Archive
Keywords: German fiction -- Translations into English